English Language Education Students’ Perception of the Use of English Subtitled Movies - Andriani, Widdi; Angelina, Patricia (Indonesian Journal of English Language Studies (IJELS), 2020)
English is an international language that most people in the world use to communicate. Video or movie is one of the effective media to be used in a language classroom. In the English Language Education Study Program (ELESPA) of Sanata Dharma University, movies with English subtitles were used in a class as a learning media. This research aims to know how ELESP students perceive English subtitled movies as learning media. There are two research questions in this research: (1) What is the ELESP students’ perception on the use of English subtitled movie? (2) What are the effects of using English subtitled movie for ELESP students? The researcher used a survey as the method in this research. The participants for this research were the students from C class batch 2016. The instruments used by the researcher were questionnaire and interview. The results of this research showed that most of the respondents had a positive perception of the use of English subtitled movies.